2018
DOI: 10.1002/jcp.26484
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism during in vitro maturation of mouse oocytes: An study using RNA interference

Abstract: In previous studies on glucose metabolism during in vitro maturation, intact cumulus-oocyte complexes (COCs) were treated with enzyme inhibitors/activators. Because inhibitors/activators may have non-specificity and/or toxicity, and culture of COCs cannot differentiate whether glucose metabolism of cumulus cells (CCs) or that of the oocyte supports oocyte maturation, results from the previous studies must be verified by silencing genes in either CCs or cumulus-denuded oocytes (DOs). In this study, RNAi was ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…For example, by culturing COCs with enzyme inhibitors, Xie et al 26 observed that while glycolysis promoted cytoplasmic maturation mainly by supplying energy, PPP facilitated cytoplasmic maturation to a greater extent through both reducing oxidative stress and supplying energy via providing glycolysis with fructose-6-phosphate. Xie et al 25 showed that although silencing either G6PD or GAPDH gene in CCs significantly impaired maturation of cocultured mouse DOs, silencing G6PD decreased oocyte competence to a greater extent. While silencing either G6PD or GAPDH in CCs decreased ATP contents of cocultured DOs to a similar extent, silencing G6PD significantly increased oxidative stress as well as decreasing ATP contents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, by culturing COCs with enzyme inhibitors, Xie et al 26 observed that while glycolysis promoted cytoplasmic maturation mainly by supplying energy, PPP facilitated cytoplasmic maturation to a greater extent through both reducing oxidative stress and supplying energy via providing glycolysis with fructose-6-phosphate. Xie et al 25 showed that although silencing either G6PD or GAPDH gene in CCs significantly impaired maturation of cocultured mouse DOs, silencing G6PD decreased oocyte competence to a greater extent. While silencing either G6PD or GAPDH in CCs decreased ATP contents of cocultured DOs to a similar extent, silencing G6PD significantly increased oxidative stress as well as decreasing ATP contents.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is the first report on the pathways by which pyruvate and lactate are utilized during maturation of pig oocytes. Our recent studies on mouse oocytes showed that inhibiting MCT with 4-CIN or suppressing ETC with rotenone in COCs, or knocking down MPC1 or NDUFV1 genes with RNAi in DOs significantly impaired pyruvate utilization and oocyte maturation 25,26 . However, how lactate is metabolized in DOs and how pyruvate and lactate are utilized in CCs to support oocyte maturation was not observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations